2011
DOI: 10.1111/j.1476-5381.2011.01480.x
|View full text |Cite
|
Sign up to set email alerts
|

System xc cystine/glutamate antiporter: an update on molecular pharmacology and roles within the CNS

Abstract: System xc-is an amino acid antiporter that typically mediates the exchange of extracellular L-cystine and intracellular L-glutamate across the cellular plasma membrane. Studied in a variety of cell types, the import of L-cystine through this transporter is critical to glutathione production and oxidative protection. The exchange-mediated export of L-glutamate takes on added significance within the CNS, as it represents a non-vesicular route of release through which this excitatory neurotransmitter can particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
365
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 429 publications
(374 citation statements)
references
References 143 publications
2
365
0
7
Order By: Relevance
“…34 While the other tested glutamatergic genes showed increased levels in fTAMs, fTAMs exhibited a near-significant decrease in xCT gene expression compared to hMGs. The decrease in xCT gene expression was observed to be statistically significant in MDMs after co-culture with glioblastoma cells compared to MDMs after co-culture with NHA.…”
Section: Discussionmentioning
confidence: 99%
“…34 While the other tested glutamatergic genes showed increased levels in fTAMs, fTAMs exhibited a near-significant decrease in xCT gene expression compared to hMGs. The decrease in xCT gene expression was observed to be statistically significant in MDMs after co-culture with glioblastoma cells compared to MDMs after co-culture with NHA.…”
Section: Discussionmentioning
confidence: 99%
“…We further assessed the effect of CPG on extracellular direct-current (DC) field potentials (46) and showed that CPG significantly reduced the ΔV o amplitude after OGD ( Figure 3C). Because CPG is also a competitive inhibitor of group I metabotropic glutamate receptors (mGluR 1 ) (47), we also tested sulfasalazine (SAS; 250 μM), another nonsubstrate inhibitor of the cystine/glutamate antiporter (44,45) with no affinity for glutamate receptors, and obtained a similar attenuation of the AD current ( Figure 3, A and B). In contrast, glutamate, which is released into the extracellular space, could be deleterious to neuronal cells and other tissues that are susceptible to excitotoxic damage.…”
Section: Introductionmentioning
confidence: 98%
“…To analyze the possible contribution of the cystine/glutamate antiporter to glutamate release during OGD, we applied S-4-carboxyphenylglycine (CPG; 250 μM) ( Figure 3A), a nonsubstrate inhibitor of the antiporter (refs. 44,45, and see also Supplemental Figure 3). We found that although CPG did not change latency to AD, it significantly reduced its amplitude ( Figure 3, A and B).…”
Section: Introductionmentioning
confidence: 99%
“…System X c -: System X c -is a cystine/glutamate antiporter that transports l-cystine into cells in exchange for glutamate (12). While system X c -is generally regarded as a mechanism to ultimately increase intracellular l-cysteine for subsequent glutathione synthesis and antioxidant protection, it could also provide a substrate for H 2 S formation.…”
Section: Olsonmentioning
confidence: 99%